Pengaruh Persepsi Harga, Cita Rasa, Kepuasan Pelanggan Terhadap Minat Beli Ulang (Repurchase Intention) Pada Rumah Makan You & Me Kabupaten Gresik - Olivier, Kevin; Priyono, Achmad Agus; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Some factors in culinary business are very important to note in order to attract costumers or preserve customers that already exist. Price perception, taste, and customer satisfaction are some factors in culinary business that must be note to run a business especially for culinary business. The purpose of this research is to determine whether there is an influence between price perception, taste, and customer satisfaction in You&Me Restaurant Gresik.This research was a quantitative research using premier data, data was obtained by spreading the questionnaire to 80 samples who has been to You&Me Restaurant at least once or more than once. The obtained and described data was used to find whether there is an influence between price perception, taste, and customer satisfaction on customer repurchase intention on You&Me Restaurant Gresik.Based on the result of this research, it can be known that there is an simultaneous influence and also partial influence between price perception, taste, and customer satisfaction on customer repurchase intention in You&Me Restaurant Gresik. Keyword : Price Perception, Taste, Customer Satisfaction, Repurchase Intention.